Concept design and simulation analysis of floating water turbine - Al-Quraishi, Mohammed Baqer Zaki Yahya; binti Mohd, Siti Syafiqah; Sarip, Shamsul; Binti Mohammad, Roslina; Mad Kaidi , Hazilah (Applied Research and Smart Technology (ARSTech), 2021)
Researchers in Malaysia are attempting to advance and develop the renewable energy sector in response to increased emissions, fossil fuel exhaustion, and the need for electricity in remote areas. Water turbines are known to have a high potential for generating electricity. This paper aims to propose a new floating turbine concept and analyse it using Computational Fluid Dynamics. In the study, finding the idea started with infaring the market needs in Malaysia and transforming them into design requirements by utilising tools like the requirement table and the objective tree. After that, the requirements were changed to a function box to understand the functionality of the turbine. A task specification table was implemented to assign the specifications and create four concepts. One of the four concepts was chosen using the evaluation chart to undergo CFD analysis. The selected concept was validated using the dynamic mesh technique in ANSYS Fluent. A grid independence study and boundary sensitivity study were conducted to ensure the accuracy of the solution. The sliding mesh technique measured the performance of the turbine. It was found that the proposed turbine has higher performance than typical Savonius turbines, from 0.1 to 0.42 and 0.8 to 1.3  (Turbine Performance) and TSR (Tip Speed Ratio), respectively.